PENGARUH PHYSICAL WORK ENVIRONMENT, KECERDASAN EMOSIONAL DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT PANORAMA JTB TOURS INDONESIA - Ananda Rinaldy Sidi, (2022)
This quantitative research was conducted to examine the real effect of the physical work environment, emotional intelligence and work discipline on employee performance. This research was conducted on the company PT JTB Tours Indonesia. The method used is saturated sampling, with a quantitative approach and the instrument is a questionnaire. Using a research sample of 50 company employees. The data analysis technique used is descriptive statistical analysis technique, inferential statistical analysis and partial significant test (t test) and simultaneous test (f test). By using the help of the smart pls 3.0 program. The results of the tests obtained are that the physical work environment has a positive and significant effect on employee performance, the emotional intelligence variable has a positive and significant effect on employee performance. work discipline has a positive and significant effect on employee performance. And the physical work environment, emotional intelligence and work discipline on employee performance have a positive and significant influence simultaneously.